The Complete Plastid Genome Sequence of Madagascar Periwinkle Catharanthus roseus (L.) G. Don: Plastid Genome Evolution, Molecular Marker Identification, and Phylogenetic Implications in Asterids. - Chuan Ku; Wan-Chia Chung; Ling-Ling Chen; Chih-Horng Kuo (PLoS ONE, 2013)
The Madagascar periwinkle (Catharanthusroseus in the family Apocynaceae) is an important medicinal plant and is the source of several widely marketed chemotherapeutic drugs. It is also commonly grown for its ornamental values and, due to ease of infection and distinctiveness of symptoms, is often used as the host for studies on phytoplasmas, an important group of uncultivated plant pathogens. To gain insights into the characteristics of apocynaceous plastid genomes (plastomes), we used a reference-assisted approach to assemble the complete plastome of C. roseus, which could be applied to other C. roseus-related studies. The C. roseus plastome is the second completely sequenced plastome in the asterid order Gentianales. We performed comparative analyses with two other representative sequences in the same order, including the complete plastome of Coffeaarabica (from the basal Gentianales family Rubiaceae) and the nearly complete plastome of Asclepiassyriaca (Apocynaceae). The results demonstrated considerable variations in gene content and plastome organization within Apocynaceae, including the presence/absence of three essential genes (i.e., accD, clpP, and ycf1) and large size changes in non-coding regions (e.g., rps2-rpoC2 and IRb-ndhF). To find plastome markers of potential utility for Catharanthus breeding and phylogenetic analyses, we identified 41 C. roseus-specific simple sequence repeats. Furthermore, five intergenic regions with high divergence between C. roseus and three other euasterids I taxa were identified as candidate markers. To resolve the euasterids I interordinal relationships, 82 plastome genes were used for phylogenetic inference. With the addition of representatives from Apocynaceae and sampling of most other asterid orders, a sister relationship between Gentianales and Solanales is supported.